RELATIONSHIP BETWEEN SECTORAL ELECTRICİIY CONSUMPTION AND ECONOMIC GROWTH IN TURKEY: APPLICATION OF MWALD-BASED CAUSALITY ANALYSIS (Third Sector Social Economic Review, 2019)
The main purpose of the article is to examine the causality relations of electricity consumption on economic growth in Turkey from a sectoral perspective. In this respect, the total electricity consumption and real gross domestic product series were used for the period 1970-2017 in Turkey as well as the electricity consumption of commercial, illumination, household, goverment, other and industrial sector on an annual basis. Toda-Yamamoto(1995) and Dolado-Lutkepohl(1996) tests using the MWALD test for the determination of causality relations between variables were used. According to the Toda-Yamamoto test results, it is observed that there is a two-way causality between electricity consumption and economic growth in commercial, household and industrial sectors. It has been determined that the growth hypothesis in terms of total electricity consumption with the government sector and the conservation hypothesis for the illumination sector are valid. In terms of the Dolado-Lutkepohl test, the conservation hypothesis for electricity consumption of other, household and illumination sectors is valid, while the remaining sectors have no causality. In addition, the validity of the conservation hypothesis for the illumination sector as a common result of both tests is noteworthy.
Keywords: Sectoral Net Electricity Consumption; Economic Growth; Electricity Consumption; MWALD Based Causality Tests; Turkey